NEO-LIBERALISM AND ORDOLIBERALISM: A critique of two forms of imperialism and authoritarianis - Fouskas, Vassilis K. (Politeia, 2019)
Imperialism is primarily driven by a combination of public policies and accumulation regimes taking place within the domestic environment of the imperial state itself. As an international policy, however, imperialism aims at transforming other states’ socioeconomic and political orders, especially in the global periphery and semi-periphery, by way of transplanting its own class model prevailing in the metropolitan home. The two most important stylised and separable, but not separate, public policies of our times are that of Anglo-American neo-liberalism, which drives post-Bretton Woods globalisation/ financialisation, and that of German-Austrian ordoliberalism, which guides the process of European ‘integration’. The argument advanced here is that (Anglo-American) neoliberalism and (German-Austrian) ordoliberalism are not stand-alone domestic policies, but are instead consubstantial with imperial undertakings. The former project is wider and truly global in scope, whereas the latter is dominating the EU/Eurozone and its immediate periphery (the Balkans/Eastern Europe and the MENA region). In this context, the article puts forth a qualitative critique of both public policies as imperial policies of domination, transformation and exploitation, buttressing regimes of permanent austerity and authoritarianism at home and permanent war and devastation abroad.
Keywords: Imperialism; New American Imperialism (NAI); Financialisation; Globalisation; Ordoliberalism; Neo-Liberalism; Core–Periphery Relations